Dietary Pattern, Hypertension and Cognitive Function in an Older Population: 10-Year Longitudinal Survey - Xiaoyue Xu; Xiaoyue Xu; Deborah Parker; Zumin Shi; Zumin Shi; Julie Byles; John Hall; Louise Hickman (Frontiers Media S.A., 2018)
Background: There is a paucity of studies that have explored the association between dietary pattern and cognitive function, and whether there is an interaction between dietary pattern and hypertension in relation to older people's cognitive functioning.Methods: We analyzed data from the China Health and Nutrition (CHNS) survey. Dietary data have been collected since 1991, and cognitive function interview data were collected between 1997 and 2006. We analyzed ten years of data, including 4,847 participants with 10,658 observations (aged ≥55 years). Exploratory factor analysis was used to identify dietary patterns. Cognitive function measures include cognitive global scores and verbal memory scores. Linear mixed models were used to investigate the association between dietary patterns, hypertension and cognitive function.Results: Three dietary patterns were identified by factor analysis, named "Traditional Chinese," "Protein-rich," and "Starch-rich" dietary pattern. A Protein-rich dietary pattern (high intake of milk, eggs and soymilk) was significantly associated with higher cognitive global scores and verbal memory scores, while the starch-rich dietary pattern (high intake of salted vegetable and legumes) was significantly associated with lower cognitive global and verbal memory scores. In addition, we found that participants with hypertension were independently associated with significant low cognitive function.Conclusion: The study reinforces the importance of diet in preventing cognitive decline among the older population. Identification of older populations who had hypertension should be targeted in intervention studies to maintain their cognitive health.